A saúde mental sob as lentes de crianças: uma pesquisa participativa inclusiva - Martins, Bruna Melo (Universidade Federal de São Carlos, 2020)
ABSTRACT - The Children and Adolescent Mental Health Brazilian Policy considers youngsters as subjects of rights. Therefore, their place of speech must be guaranteed in the mental health care context. Despite recent advances in the understanding of child and adolescent mental health, the prevailing concepts remain anchored in a biomedical perspective, with little regard for the perceptions of the main stakeholders. Studies that propose participatory discussions, reflections and actions approaching the realities of experiencing psychological distress in childhood offer elements arising from the children's own understandings about mental health, as well as aspects that may be involved in this condition, and can contribute to more effective assistance strategies for this population. Thus, the present study aimed to identify the understanding of children aged 9-11 years about mental health and also about what favors it and what harms it. A participatory investigation was carried out with a group of 23 children bonded to an after-school program. All ethical aspects were considered. Data collection involved the development of collective and individual activities, namely: development of children's newscasts with the theme “What is Mental Health?”; drawing illustrations about what they consider “good mental health” and “bad mental health” and, finally, the collective creation of posters on what favors and harms mental health - the latter being developed through photovoice strategy. Horizontality and playfulness were sought and valued throughout the research process and the emerging data were analyzed together with the children. Results revealed that children understand that mental health is related to occupations and situations that either generate pleasure, learning and well-being (sports, playing, learning), or suffering (violence and substance abuse). Playing, sports and studies were identified as elements that promote good mental health in childhood and on the other hand, violence in its various possibilities of expression was identified as harmful - corroborating what has been signaled by scholars in the field. It was found that the children showed clarity about what affects them. Therefore, considering their perspectives beyond the adult perspective seems to be a path for the policymaking processes and actions that indeed aim to protect them.

RESUMEN - La Política Brasileña de Salud Mental Infanto-Juvenil considera a los niños y a los adolescentes como sujetos de derecho y, por tanto, estos deben tener garantizado su lugar de habla en el contexto de cuidado de salud mental. A pesar de los recientes avances en lo que se refiere a la comprensión de la salud mental infanto-juvenil, los conceptos predominantes aún permanecen anclados en una perspectiva biomédica, con poca consideración en las percepciones de los actores envueltos. En este sentido, estudios que se propongan desarrollar, de manera participativa, discusiones, reflexiones y acciones que se aproximen a las realidades de la vivencia del sufrimiento psíquico en la infancia, y que ofrezcan elementos surgidos de las compresiones de los propios niños sobre la salud mental, como también lo que puede estar implicado en esa condición, logran contribuir con estrategias más efectivas de asistencia a ese público. Así, el presente estudio tuvo como objetivo identificar la compresión de niños de 9 a 11 años de edad sobre la salud mental y sobre lo que la favorece o la perjudica. Fue realizada una investigación de naturaleza participativa con un grupo de 23 niños vinculados a una institución que ofrece actividades en un período contrario a la escuela de estos. Todos los aspectos éticos fueron considerados. La producción de datos envolvió el desarrollo de actividades colectivas e individuales: elaboración de noticieros infantiles con el tema “¿Qué es la Salud Mental?”; creación de dibujos ilustrativos sobre lo que consideraban una “salud mental buena” y una “salud mental mala”, y, finalmente, la confección colectiva de carteles cuyo tema radicó en lo que favorece y perjudica la salud mental –esta última actividad fue hecha a través de la estrategia de foto-voz–. La horizontalidad y la ludicidad fueron buscadas y valorizadas durante todo el proceso de la investigación; a su vez, los datos emergentes fueron analizados en conjunto con los niños. Los resultados producidos revelaron que los niños comprenden que la salud mental está relacionada a ocupaciones y situaciones que, o generan placer, aprendizaje y bienestar (prácticas deportivas, jugar, aprender), o sufrimiento (violencia y uso abusivo de substancias). El juego, los deportes y los estudios fueron identificados como elementos motores de la buena salud mental en la infancia y, por otro lado, la violencia, en sus diversas formas de expresión, fue señalada como perjudicial –corroborando con lo que había sido apuntado por estudiosos del área–. Se verificó que los niños demostraran claridad sobre aquello que les afectaba, lo que, por tanto, potencia la consideración de sus perspectivas, las cuales van más allá de la óptica adulta, transformando lo que parece ser un camino para los procesos de elaboración de políticas y acciones que, seriamente, busquen protegerlas.
Mental health under the lens of children: an inclusive participatory research
Keywords: Saúde mental infanto-juvenil; Crianças; Pesquisa participativa; Terapia ocupacional; Child and adolescent mental health; Children; Participatory research; Occupational therapy; Salud mental infanto-juvenil; Niños; Investigación participativa; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL